Introducing the SISM Model– A Holistic Approach to SMME Incubation Programmes - Mwale, Bongani, June; Nyamkure Ph.D, Professor Dr. Blondel; Costa, King (My University, 2021)
Background: Business incubators provide specialised training and mentorship support to upcoming small to medium businesses. There has been a number of incubation programmes in Gauteng province of South Africa. It has been observed that sometimes, some incubation centres fail to achieve objectives for which they were created and originated. That failure results in losses, particularly for those who had created them and as well as loss of income, time and related resources to the beneficiaries, usually the helpless and needy grassroots SMMEs. As a result, some initiatives through incubation are losing the confidence of those who should benefit or support them, due to the failures related to application and operationalization. In view of the above, this study sought to determine and assess the expected effectiveness and significance of business incubation services on turnover of the Gauteng Province tourism SMMEs sector. Methods: The orientation of this study was hinged upon positivist paradigm with an objective ontological position. By virtue, a random sampling procedure of 103 participants using questionnaires for data collection was used in the study. Moreover, the Cronbach’s alpha and Keiser-Meyer-Olkin techniques were used and resulted in the conclusion that the study was structurally valid and reliable. This entailed a critique of the strategies that could optimally support the effective and efficient provision and growth of SMMEs within the tourism sector of the Province. The study achieved that result by using paired-samples t-tests, principal component analysis, frequencies, exploratory factor analysis, and descriptive statistical techniques to evaluate four hypotheses at a 5% level of significance. Results: Empirical findings indicated that the respondents (SMMEs Business Owners and Managers) had a certain level of expectation regarding the incubation programme, such as support, training and business linkages. This expectation was mainly directed to the provincial government as he custodian of economic development and growth. Interestingly, the study found out that despite lack of confidence on similar initiatives (SMMEs incubation prgrammes), and much reported failures, SMME owners felt there was a need for this type of intervention but caution needs to be exercised in terms of operationalization and sustainability. Discussion: In this synthesis, current trends, events and practice on a global, regional and local perspectives are closely securitized. Evidence shows that incubators have been successful in encouraging the development of new start-ups by reducing the failure rate of small- and medium-sized companies (Mirza & Rahmani, 2017). Incubators have become highly popular as a way of cultivating start-ups in both developed and developing countries, whereby they form integral for providing assistance to young businesses in enabling structures (Lalkaka, 2006). Having discovered their value, all those working in the incubation industry continue to seek to discover, describe, calculate, devise, and rate the different aspects of incubation as a sustainable intervention. For that reason, he SISM Model is hereby introduced.
Keywords: Business Incubators; Model; Planning; Strategy; SMMEs